2009
DOI: 10.1021/es9019518
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Mercury Isotopic Compositions of Fish and Human Hair in the Bolivian Amazon

Abstract: We report mercury (Hg) mass-dependent isotope fractionation (MDF) and mass-independent isotope fractionation (MIF) in hair samples of the Bolivian Esse Ejjas native people and in several tropical fish species that constitute their daily diet. MDF with δ202Hg ranging from −0.40 to −0.92 ‰ for fish and +1.04 to +1.42 ‰ for hair was observed. Hair samples of native people with a fish-dominated diet are enriched by +2.0 ± 0.2 ‰ in δ202Hg relative to the fish consumed. Both odd Hg isotopes, 199Hg and 201Hg, display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
162
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(199 citation statements)
references
References 36 publications
(71 reference statements)
31
162
6
Order By: Relevance
“…Although there are many industries that may release Hg into LM, Hg used in industry is primarily derived from mining, and therefore should exhibit similar signatures. Previous results on Hg ores other metal deposits exhibited d 202 Hg of ∼ -0.6±0.4‰ (σ) and D 199 Hg close to 0 (Sonke et al, 2010;Liu et al, 2011;Blum et al, 2014;Hintelmann and Lu, 2003;Smith et al, 2005Smith et al, , 2008Stetson et al, 2009;Laffont et al, 2011;Yin et al, 2013a). Sediments with high THg concentrations is predominately derived from anthropogenic sources as deposition typically occurs near the source, waters are relatively turbid (thereby reducing photochemical processes) or the Hg from these sources are less susceptible to photo-reduction (Foucher and Hintelmann, 2009;Feng et al, 2010;Gehrke et al, 2011;Sonke et al, 2010;Donovan et al, 2013;Cooke et al, 2013;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2013Gray et al, , 2015Balogh et al, 2015;Yin et al, 2013a;Lepak et al, 2016 …”
Section: Historical Records Of Dmentioning
confidence: 91%
“…Although there are many industries that may release Hg into LM, Hg used in industry is primarily derived from mining, and therefore should exhibit similar signatures. Previous results on Hg ores other metal deposits exhibited d 202 Hg of ∼ -0.6±0.4‰ (σ) and D 199 Hg close to 0 (Sonke et al, 2010;Liu et al, 2011;Blum et al, 2014;Hintelmann and Lu, 2003;Smith et al, 2005Smith et al, , 2008Stetson et al, 2009;Laffont et al, 2011;Yin et al, 2013a). Sediments with high THg concentrations is predominately derived from anthropogenic sources as deposition typically occurs near the source, waters are relatively turbid (thereby reducing photochemical processes) or the Hg from these sources are less susceptible to photo-reduction (Foucher and Hintelmann, 2009;Feng et al, 2010;Gehrke et al, 2011;Sonke et al, 2010;Donovan et al, 2013;Cooke et al, 2013;Ma et al, 2013;Mil-Homens et al, 2013;Gray et al, 2013Gray et al, , 2015Balogh et al, 2015;Yin et al, 2013a;Lepak et al, 2016 …”
Section: Historical Records Of Dmentioning
confidence: 91%
“…The discovery of mass dependent fractionation (MDF) and mass independent fractionation (MIF) of mercury isotopes Hg Schauble, 2007;Biswas et al, 2008;Ghosh et al, 2008;Carignan et al, 2009;Das et al, 2009Das et al, , 2013Laffont et al, 2009;Sherman et al, 2009Sherman et al, , 2010Sherman et al, , 2012Sonke, 2011;Chen et al, 2012;Jackson andMuir, 2012, Perrot et al, 2012;Sonke and Blum, 2013). MIF of an isotope of even mass number ( 200 Hg) has also been detected in atmospheric Hg (Gratz et al, 2010;Chen et al, 2012;Sherman et al, 2012, Rolison et al, 2013, Wang et al, 2015 and has been suggested to be caused by photo-induced oxidation of GEM on the surfaces of aerosols and particles in the tropopause (Chen et al, 2012).…”
Section: Domain Editor-in-chiefmentioning
confidence: 99%
“…Positive MIFs were also observed in human hair (Point et al, 2011;Day et al, 2012) and they are generally related to seafood consumption (Laffont et al, 2011;Blum et al, 2014). On the other hand, MDF has been revealed in human hair, resulting in a~þ2‰ d 202 Hg offset with respect to the consumed seafood (Laffont et al, 2009;. The Augusta Bay (AB; SE Sicily) is a wellknown case study where the Hg sewages from the largest Italian chlor-alkali plant (1958e2005) (Le Donne and Ciafani, 2008) caused alarming environmental concerns (ICRAM, 2005(ICRAM, , 2008Sprovieri et al, 2011), strongly impact on the trophic web (Ausili et al, 2008;Tomasello et al, 2012;Bonsignore et al, 2013) and evasional flux of Hg into atmosphere (Bagnato et al, 2013).…”
Section: Introductionmentioning
confidence: 95%